A de novo ACTB gene pathogenic variant in identical twins with phenotypic variation for hydrops and jejunal atresia. Issue 4 (31st December 2021) - Sibbin, Kristina; Yap, Patrick; Nyaga, Denis; Heller, Raoul; Evans, Stephen; Strachan, Kate; Alburaiky, Salam; Nguyen, Han M. (Alex); Hermann‐Le Denmat, Sylvie; Ganley, Austen R. D.; O'Sullivan, Justin M.; Bloomfield, Frank H.
Abstract: The beta‐actin gene ( ACTB ) encodes a ubiquitous cytoskeletal protein, essential for embryonic development in humans. De novo heterozygous missense variants in the ACTB are implicated in causing Baraitser–Winter cerebrofrontofacial syndrome (BWCFFS; MIM#243310). ACTB pathogenic variants are rarely associated with intestinal malformations. We report on a rare case of monozygotic twins presenting with proximal small bowel atresia and hydrops in one, and apple‐peel bowel atresia and laryngeal dysgenesis in the other. The twin with hydrops could not be resuscitated. Intensive and surgical care was provided to the surviving twin. Rapid trio genome sequencing identified a de novo missense variant in ACTB (NM_00101.3:c.1043C>T; p.(Ser348Leu)) that guided the care plan. The identical variant subsequently was identified in the demised twin. To characterize the functional effect, the variant was recreated as a pseudoheterozygote in a haploid wild‐type S. cerevisiae strain. There was an obvious growth defect of the y ACT1 S348L/WT pseudoheterozygote compared to a y ACT1 WT/WT strain when grown at 22°C but not when grown at 30°C, consistent with the y ACT1 S348L variant having a functional defect that is dominant over the wild‐type allele. The functional results provide supporting evidence that the Ser348Leu variant is likely to be a pathogenic variant, including being associated with intestinal malformations in BWCFFS, and can demonstrate variable expressivity within monozygotic twins.